Main areas of EU — Latin America & Caribbean bi-regional cooperation (case study of EU — CELAC summits) - V. D. Elnikova (Проблемы постсоветского пространства, 2019)
The article analyzes key documents of the European Union (EU) related with its external policy towards Latin America and the Caribbean, as well as its practical implications. The Maastricht Treaty created bases for the common external policy of the European Union. The EU strategy towards Latin America is reflected in the Multiannual Indicative Regional Programme 2014-2020. The document states the progress achieved, continuing challenges, priority areas and amount of the financial aid.Currently the joint summits between the European Union and the Community of Latin American and the Caribbean States (EU–CALAC) serve as a main dialogue field enabling cooperation between the two regions. The main areas of collaboration are: democracy and human rights, security, trade and investment, innovations and education, climate change. Apart the EU provides a significant financial support to Latin America and the Caribbean (LAC) through sector programmes aimed at social and economic transformations in LAC. In order to encourage investment the parties established Latin American Investment Facility (LAIF). The European Union and the Caribbean Foundation (EU–LAC Fundation) serves as an additional tool to promote and strengthen strategic cooperation between the two regions.